2016
DOI: 10.3402/tellusb.v68.30659
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation and source apportionment of PM<sub>1</sub> during massive loading at an urban location in Indo-Gangetic Plain: impact of local sources and long-range transport

Abstract: A B S T R A C TThis study assesses temporal variability and source contributions of PM 1 (particles with aerodynamic diameter 5 1.0 mm) samples (n051; November 2009ÁFebruary 2010) from an urban location at Kanpur (26.308N; 80.138E; 142 m above mean sea-level) in the Indo-Gangetic Plain (IGP). A study period from November to February is preferred owing to massive loading of particulate matter in entire IGP. PM 1 varies from 18 to 348 (Avg9SD: 113972) mg m (3 in this study. A total of 11 trace metals, five major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 25 publications
5
16
0
Order By: Relevance
“…The average NO 3 − /SO 4 2− mass ratio < 1 can be attributed to predominant impact from stationary source/s (biomass burning, coal combustion and industrial emission), whereas the NO 3 − /SO 4 2− mass ratio ≥ 1 indicates predominant impact from mobile source (vehicular emissions) (Wu et al 2017). A recent study based on positive matrix factorization (PMF) has reported similar results with the NO 3 − /SO 4 2− mass ratio in IGP (Rajput et al 2016b).…”
Section: Inferences From Anthropogenic Inorganic Speciessupporting
confidence: 62%
See 1 more Smart Citation
“…The average NO 3 − /SO 4 2− mass ratio < 1 can be attributed to predominant impact from stationary source/s (biomass burning, coal combustion and industrial emission), whereas the NO 3 − /SO 4 2− mass ratio ≥ 1 indicates predominant impact from mobile source (vehicular emissions) (Wu et al 2017). A recent study based on positive matrix factorization (PMF) has reported similar results with the NO 3 − /SO 4 2− mass ratio in IGP (Rajput et al 2016b).…”
Section: Inferences From Anthropogenic Inorganic Speciessupporting
confidence: 62%
“…9a) suggested that NH 4 + was in excess. In this context, previous studies have reported that excess NH 4 + can lead to uptake of NO 3 − in the particulate phase (Pathak et al 2009;Rajput et al 2016b). Furthermore, the NO 3 − /SO 4 2− average mass ratio was 0.71 ± 0.33 in this study (Fig.…”
Section: Inferences From Anthropogenic Inorganic Speciessupporting
confidence: 53%
“…Unlike PM 2.5 and PM 10 , PM 1 originates almost entirely from two sources: direct emissions 97 during combustion process, and indirectly, from formation of particles in the air from gaseous 98 precursors (Rajput et al, 2016;Singhai et al, 2016). By contrast, PM 10 is mostly emitted by 99 mechanical processes, such as construction activities, or by wind re-suspension (of for 100 example loose soil).…”
mentioning
confidence: 99%
“…Concentration of K ? in aqueous extracts has been measured on an ionchromatograph (Metrohm) (Chakraborty and Gupta 2010;Gupta and Mandaria 2013;Rajput et al 2016b). To assess the quality control of data, blank filters (n = 4) were simultaneously processed and analyzed along with aerosol samples in the similar manner.…”
Section: Aerosol Sampling and Analytical Detailsmentioning
confidence: 99%
“…It should be noted that herein synergy represents the lensing effect between BrC (shell/coating) and EC (core) aerosols. The IGP is stretched from north-west to north-east region in India, which is considered as one of the most polluted and populated regions of the world (Kaul et al 2011;Rajput et al 2011Rajput et al , 2013Rajput et al , 2015Rajput et al , 2016b. This study was strategically conducted over central IGP during a monsoon season (July-September 2015) influenced by El Niño and PDO.…”
Section: Introductionmentioning
confidence: 99%